Pola pasien anemia yang berkunjung ke Poliklinik Hematologi RSUP Sanglah dari April 2015-April 2017 - Ni Made Ayu Sintya D; I Wayan Losen Adnyana; IGP Suka Aryana (Intisari Sains Medis, 2020)
Introduction: Anemia is a clinical condition associated with many causes. Anemia is not a disease, it is a syndrome and generally described as a decreased of red blood cell mass and hemoglobin below the normal level. Based on WHO's criteria, someone can be diagnosed with anemia if their hemoglobin level falls below 130 g/L for men and below 120 g/L for women. Based on a survey made by WHO, about one from every four people in the world suffered from anemia.Aim: The study aims to evaluate the patient arrival pattern to the Hematological Policlinic in RSUP Sanglah Denpasar.Â Method: This is analytic observational research of the anemic patient who came to the Hematological Policlinic in Sanglah General Hospital from April 2015-April 2017.Result: The highest proportion of anemic patient who came to Hematologic Policlinic in Sanglah General Hospital based on age classification are the age group of 15-59 while based on sexes the percentage of the anemic male patient is 44.2%, and the anemic female is 55.8% while 2.9% of that female is currently pregnant.Conclusion: From the causative point of view, the anemic patient in Hematologic Policlinic in Sanglah General Hospital from April 2015 to April 2017 mostly diagnosed with unspecified type while 58.7% of the anemic patient come without another health issues and the other 41.3% have had underlying or accompanying diseases.Introduction: Anemia merupakan suatu kondisi klinis yang diasosiasikan dengan banyak penyebab. Anemia bukan merupakan suatu penyakit melainkan suatu syndrome dan pada umumnya didefinisikan sebagai penurunan sel darah merah dan hemoglobin di bawah nilai normal. Berdasarkan kriteria WHO, seseorang dapat didiagnosis Anemia jika hemoglobinnya berada di bawah 130 g/L untuk laki-laki dan di bawah 120 g/L untuk perempuan. Berdasarkan survey yang dibuat oleh WHO, anemia diderita oleh satu dari empat orang di dunia.Tujuan: Penelitian ini bertujuan untuk mengetahui pola kunjungan pasien ke Poliklinik Hematologi RSUP Sangah Denpasar.Metode: Penelitian ini merupakan suatu penelitian observasional pada pasien anemia yang datang ke poliklinik hematologi RSUP Sanglah dari April 2015-April 2017.Hasil: Berdasarkan penelitian ini dapat dikonklusikan bahwa proporsi tertinggi pasien anemia yang datang ke Poliklinik Hematologi RSUP Sanglah paling banyak adalah dari kelompok umur 15-19 tahun. Sementara itu, berdasarkan kelompok jenis kelamin ditemukan bahwa presentasi pasien anemia perempuan adalah 55,8% dengan 2,9% dari pasien tersebut sedang dalam keadaan hamil sementara pasien anemia laki-laki adalah 44,2%.Simpulan: Dilihat dari penyebabnya pasien anemia yang datang ke Poliklinik Hematologi RSUP Sanglah dari April 2015-April 2017 paling banyak didiagnosis dengan tipe tidak terspesifikasi dengan 58,7% pasien anemia datang tanpa disertai penyakit lain dan 41,3% datang dengan penyakit penyerta.